2016
DOI: 10.1111/pops.12352
|View full text |Cite
|
Sign up to set email alerts
|

The Social Causes and Political Consequences of Group Empathy

Abstract: Recent scholarship has discovered significant racial/ethnic group variation in response to political threats such as immigration and terrorism. Surprisingly, minority groups often simultaneously perceive themselves to be at greater risk from such threats and yet still prefer more open immigration policies and civil liberties protections. We suggest a group‐level empathy process may explain this puzzle: Due to their higher levels of empathy for other disadvantaged groups, many minority group members support pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 50 publications
(67 reference statements)
1
31
0
Order By: Relevance
“…members (21). Observational work also suggests that differing levels of empathy explain varying political attitudes across racial groups (22,23). There is therefore a scientific basis for the idea that a perspective-taking treatment may result in more inclusionary attitudes toward refugees.…”
Section: Significancementioning
confidence: 99%
“…members (21). Observational work also suggests that differing levels of empathy explain varying political attitudes across racial groups (22,23). There is therefore a scientific basis for the idea that a perspective-taking treatment may result in more inclusionary attitudes toward refugees.…”
Section: Significancementioning
confidence: 99%
“…One explanation for this weak association is that human empathy is subject to powerful regulation, even when empathic responses occur automatically. There are numerous factors that affect the up‐ and down‐regulation of empathy including the number of people who require help, whether the affected person is a member of one’s ingroup, one’s level of concern for members of disadvantaged outgroups, personal distress, and the anticipated pain or other negative states associated with empathy (Cameron & Payne, ; Decety, ; Sirin, Valentino, & Villalobos, ). We focus here on a belief in individualism to assess what happens when empathy and individualism conflict.…”
Section: Empathic Ability and Its Regulationmentioning
confidence: 99%
“…For example, psychology research demonstrates that feelings of empathic concern for a member of a stigmatized group, such as a homeless person or an AIDS victim, can reduce stigmatization and prejudice (e.g., Batson et al 1997; Batson et al 2002). Other research has shown that empathy for racial and ethnic groups can generate higher support for civil rights policies that protect undocumented immigrants and suspected terrorists (Sirin, Valentino, and Villalobos 2016, 2017). Perhaps inspired by this research, then-Senator Barack Obama identified an “empathy deficit” as the root of many problems in American politics (for a scholarly take on the topic, see Ditto and Koleva 2011).…”
mentioning
confidence: 99%
“…Many of the more optimistic findings regarding empathy’s utility in reducing conflict come from laboratory experiments involving direct manipulations of the experience of empathy, but the effects derived from forced exposure experiments may differ from those under self-selection (for discussion, see Gaines and Kuklinski 2011). This methodological point is crucial because people are systematically biased in how they experience empathy on a day-to-day basis (Bloom 2016) and tend to display greater empathy toward ingroup members (Sirin, Valentino, and Villalobos 2017). When given the choice, people seek out environments that minimize contact with dissimilar others and ideas (e.g., Flache and Macy 2011; Gimpel and Hui 2015; Hart et al 2009; Sears and Freedman 1967).…”
mentioning
confidence: 99%